2015
DOI: 10.5858/arpa.2015-0296-oa
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Frozen Section Diagnosis for Axillary Sentinel Lymph Nodes as a Result of the American College of Surgeons Oncology Group Z0011 Trial

Abstract: Context.-Results of the American College of SurgeonsOncology Group Z0011 trial showed that patients with early-stage breast cancer and limited sentinel node metastasis treated with breast conservation and systemic therapy did not benefit from axillary lymph node dissection. Subsequently, most pathology departments have likely seen a decrease in frozen section diagnosis of sentinel lymph nodes.Objective.-To determine the effect of the Z0011 trial on pathology practice and to examine the utility of intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…15 In our previous report, the use of frozen section dropped from 55% in the first 6 months to 22% in the last 6 months. Several groups have reported on the decreased use of SLN frozen section after Z0011, 25, 26 which decreases operative time and provides cost savings. 15, 25, 27 Fillion et al showed that eliminating intra-operative assessment decreases the cost of SLND from $4319 to $2036, with a further 20% cost reduction per patient in which ALND was avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In our previous report, the use of frozen section dropped from 55% in the first 6 months to 22% in the last 6 months. Several groups have reported on the decreased use of SLN frozen section after Z0011, 25, 26 which decreases operative time and provides cost savings. 15, 25, 27 Fillion et al showed that eliminating intra-operative assessment decreases the cost of SLND from $4319 to $2036, with a further 20% cost reduction per patient in which ALND was avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported on the decreased use of SLN frozen section after Z0011, 25, 26 which decreases operative time and provides cost savings. 15, 25, 27 Fillion et al showed that eliminating intra-operative assessment decreases the cost of SLND from $4319 to $2036, with a further 20% cost reduction per patient in which ALND was avoided. 27 Given these observations and the lack of oncologic benefit to additional axillary surgery, the American Society of Breast Surgeons included omission of ALND in appropriate SLN-positive patients in their Choosing Wisely® Campaign.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative pathologic assessment of SLNs is desirable, because it may spare the patient a second operation if a preoperative decision has been made to proceed with completion axillary lymph node dissection (ALND) in case of positive SLN(s) 36. Frozen section (FS) remains the most popular means of intraoperative SLN diagnosis in many centers although the overall rate of intraoperative SLN pathologic assessment appears to be declining, probably as an aftermath of the American College of Surgeons Oncology Group Z0011 Trial 7. The use of FS is accompanied with many drawbacks such as considerable waiting time, tissue loss, and cost.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a lot of studies have questioned the role of a routine FS for SLNBx in early breast cancer. [14,15] Rónká et al in a prospective trial showed that, with respect to hospital costs, FS analysis seems to be worthwhile as long as the false-negative rate does not exceed 35%. [16] The false-negative rate in our study was 3.22% which meets international standards.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, routine FS diagnosis for sentinel lymph node biopsies can be avoided in these patients. [14] Leonardo Russo in a retrospective analysis of 281 patients showed that comprehensive information of the definitive histopathological findings either of the primary tumour and SLNs may help in making a better decision to completion ALND without an intraoperative FS analysis. The false-negative rate in SLN with macrometastasis was 13.1% and for micrometastasis cases was 66.7% (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%